Mystery cults in visual representation in Graeco-Roman antiquity - Belayche, Nicole; Massa, Francesco (Religions in the Graeco-Roman world, 2021)
Contents -- List of Illustrations -- List of Contributors -- 1 Mystery Cults and Visual Language in Graeco-Roman Antiquity: an Introduction -- Nicole Belayche and Francesco Massa -- part 1: Do Images Depict Mystery Cults, and If So, How? -- 2 Sub-Introduction -- 3 Comment figurer l'ineffable, comment lire les images? -- Cornelia Isler-Kerényi -- 4 Le phallus qui cache le mystère? Les images dionysiaques dans les décors romains: à propos d'une fresque de la Domus Transitoria -- Stéphanie Wyler -- 5 Échos de la Télétè dionysiaque dans la mosaïque romaine tardive -- Janine Balty -- part 2: Historiography and Images of Mystery Cults -- 6 Sub-Introduction -- 7 'The Seven Grades of Mithraism', or How to Build a Religion -- Philippa Adrych -- 8 Les mystères isiaques et leurs expressions figurées. Des exégèses modernes aux allusions antiques -- Richard Veymiers -- part 3: Depicting Objects to Signify Mystery Cults -- 9 Sub-Introduction -- 10 The Liknon and the Bundle: Does the Ritual 'Initiatory' Object Make the Mystery? -- Anne-Françoise Jaccottet -- 11 The Cista, a Hallmark of Mater Magna's Mysteries in the Roman World? -- Françoise Van Haeperen -- Selected Bibliography -- Index.